Combined Use of the Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratios as a Prognostic Predictor in Patients with Operable Soft Tissue Sarcoma - Liang, Yao (J Cancer, 2018)
Background: Preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are associated with poor prognosis in soft tissue sarcoma (STS). The aim of the present study is to determine whether the combination of NLR and PLR (CNP) can better predict patient survival after resection for STS. Methods: We included 310 STS patients in this retrospective study. Preoperative CNP was calculated as follows: patients with both elevated NLR (>2.51) and PLR (>191.1) were given a score of 2; patients showing an increase in one or neither were allocated a score of 1 or 0, respectively. Results: Cut-off values of 2.51 and 191.1 were defined as elevated NLR and PLR, respectively. Elevated CNP was significantly associated with older age (P=0.034), larger tumor size (P=0.025), deeper tumor location (P=0.044), higher tumor grade (P=0.028), a more advanced stage according to the American Joint Committee on Cancer (AJCC) (P=0.005), shorter overall survival (OS) (P=0.000) and shorter disease-free survival (DFS) (P=0.000). Multivariate analysis indicated CNP but not NLR or PLR to be an independent prognostic factor for OS and DFS (P=0.000 and P=0.001, respectively). Conclusions: Preoperative CNP is associated with tumor progression and can be considered an independent marker of postoperative survival in patients with STS.